Studi Standarisasi Radioterapi Cobalt-60 Terhadap Kuantitas Sel Darah Pada Penderita Kanker Serviks (Cancer Cervics) Di Rsup Sanglah Denpasar - Oeta Ulan, Retianingsih; Sutapa, Gusti Ngurah; Sudarsana, Wayan Balik (BULETIN FISIKA; Vol 18 No 2 (2017): BULETIN FISIKA, 2017)
After doing research with Title Study of Cobalt-60 radiotherapy Standards Against Quantity Blood Cells In Patients with Cervical Cancer (Cancer Cervics) at Sanglah Hospital in Denpasar. This study uses secondary data such as a complete blood from each patient with cervical cancer in 2015 that radiotherapy with fractionation method. The amount of patient data used in this study is 5 pieces. The quantity of blood cells that are analyzed include RBC, HGB, WBC and WBC Components (LY, EO, EO, BA, NE, MO). Fractionation dose is 800-5800cGy. The results of data analysis showed that each blood cell components are still within the range of 2-50%, so a method of radiotherapy is still fit for use.